Termite-inspired metamaterials for flow-active building envelopes - Andréen, David; Soar, Rupert (Frontiers in Materials, 2023)
In this article we investigate the performative potential of reticulated tunnel networks to act as drivers for selective airflows in building envelopes and thereby facilitate semi-passive climate regulation. We explore whether such transient flow can be used to create functionally graded metamaterials in bio-inspired, additively fabricated buildings. T0068e tunnel networks are modelled on the egress complex found in the mound of certain macrotermite species. The hypothesis we explore is that oscillating airflow of low amplitude can be used to generate large scale turbulence within the network and thereby increase the mass transfer rates across the network. The hypothesis is tested through a series of 3-dimensional and 2-dimensional experiments where various geometries are exposed to a forced oscillation of the air or water column. The results are evaluated in the 3-dimesional experiments through tracer gas measurements, and in the 2-dimenstional experiments through visual qualitative assessment using fluorescein dye. We find that the oscillating fluid gives rise to large scale turbulence that causes a net mass transport across the tunnel network, and that this turbulence occurs when certain combinations of amplitude, frequency, and network geometry are achieved. Furthermore, we conclude that the net mass transfer is large enough to be functionally useful in a building envelope as a method to regulate either building interior climate or the envelope’s own microclimate.